Exploring the potential for a community-schools model to reduce school violence - Barling, Monique (Department of Social Development, 2023)
An exploratory, qualitative approach was adopted for this study. It was carried out on a sample of thirteen individual respondents using face-to-face, in-depth interviews. This sample group comprised of four educators, one school governing board member, three Non-Governmental Organisation representatives and five key informants from schoollinked and/or government institutions. Furthermore, the focus groups were conducted (two groups at School A and one group at School B). Semi-structured interview schedules were designed for the individual in-depth interviews and for the focus groups. Purposive, non-probability sampling was used in this study since respondents who could provide rich information were targeted. The main findings of this study were: That most of the respondents felt that schools act as a microcosm of the immediate environment. All respondents had been exposed to various types and forms of school violence. That respondents felt that government departments have fragmented service delivery with regards to safety measures and programming in schools. That all the respondents valued the Community Schools Model (CSM) for its potential to address the South African educational context. That NGO respondents were clear that some adaptations were needed for a CSM to be viable in reducing school violence. Finally, that this model has the potential for having a ripple effect into the adjoining communities. The main recommendations are: That the Department of Education needs a more comprehensive and updated policy on school violence. That a preliminary proposal for a Community-School Model to Reduce Violence was suggested. That immediate action and further research is to be undertaken for the growing problem of school violence.